A Public Pastoral Care Home-Based Programme Supporting Orphans Infected and/or Affected by Hiv/Aids in the Sandf: A Practical Theological Engagement - Roos, Pieter (University of the Free State, 2014)
The rationale for this study was a desire to assist some of the alarmingly high number of orphaned children (especially in Sub-Saharan Africa) who are infected and/or affected by HIV/AIDS, and who find themselves in an instant crisis after the loss of their parents as a result of the pandemic. In such a crisis, young childrenâs normal support systems are often stripped away.This study is grounded in practical theology. It adopted a postmodern paradigm, with social constructionist discourse, as its epistemological point of departure, and narrative pastoral care/therapy as the counselling approach chosen to assist HIV/AIDS orphans. In a broader sense, theologically, the study is grounded in a public theological orientation, and holistic Biblical anthropological paradigms were explored to give meaning to peopleâs broken lives.The study argues for a wider community-oriented approach to assist HIV/AIDS orphans to (re)build their lives with hope and faith by assisting them in being (re)integrated into normal society with the maximum possible support systems available to them, using a home-based care approach, rather than institutional care.Methodologically speaking, qualitative research methods were used in the study, because qualitative researchers emphasize the value-laden nature of scientific inquiry. They seek answers to questions that emphasise how social experience is created and given meaning. In this study, the following proven research methods were used: participation action research methods complemented by scientifically designed case studies, questionnaires and focus groups. Three orphans who had lost their parents due to HIV- and AIDS-related illnesses agreed to participate in the research as co-researchers. They entered into conversation with the researcher. Later, focus group work was added, involving various caregivers and a multi-professional team. As a result of this study a unique public pastoral home-based programme supporting orphans who are infected or affected by HIV/AIDS has been created within the context of the South African National Defence Force (SANDF) and led by the SANDF Chaplaincy. This programme can easily be expanded to other contexts outside the military.The unique feature of this study was that researcher made effective use of participation action research methods in all stages of the research process. The orphans were regarded as co-researchers from the beginning and their input was seen as significant to the eventual outcome of the research. Because they could participate throughout the research process, their social constructions of being infected and/or affected by HIV/AIDS were regarded as essential indicators of how they gave meaning to their lives.In order for the co-researchers to move from dominant âproblem-saturatedâ life stories to new alternative stories of hope and meaningful life, the research process involved interactive collaboration with different role players. The use of a public theological orientation and holistic Biblical anthropological paradigms as the basis for the research made it possible for other co-researchers to be invited into the process. After interacting with the orphans through scientifically designed case studies and questionnaires, various care givers, including multi-professional care personnel, took part in Appreciative inquiry focus groups. In a very short time, these discussions elicited alternative and preferred life options that assisted the orphans in mapping the direction of exciting new life scenarios.The key outcome of this study is its demonstration of how the underlying value-based Biblical-anthropological hope orientation adopted by the researcher can be applied in a contextual narrative pastoral approach to assist HIV/AIDS orphans. By making use of different methods, such as Biblical pastoral care and narrative therapy, Appreciative inquiry focus groups with key public and professional role players, and other qualitative scientific analysis, the study succeeded in developing guidelines for a useful public pastoral care home-based programme for the military, as well as in broader society.
Free
Keywords: Practical Theology